Impact of Community Forestry on Income Distribution in Nepal: Particularly on Poor-Rich Gap - Sharma, Anuja Raj (Journal of Income Distribution®, 2020)
Community forestry is one of the major programme that is being implemented in Nepal for last three decades. The programme with twin goals: nature conservation and poverty reduction is believed to be faring well with the first goal. The paper exclusively focuses on the impact of community forestry on income distribution and reviews relevant studies with the conclusion that community forestry has contributed in poverty reduction and intensive management expedites the whole process.